A study to Assess the Awareness And Practice of Fast Food Consumption and Hazards on Health among Adolescents in Urban Community Area of Pune City - Ranjana Chavan1 , Sharadha Ramesh2 , Mangesh Jabade3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction:Food is something everyone needs, every day. Life can be sustained only with adequatenourishment and it requires for growth, development and to lead an active and healthy life. Fast food refersto fast foods which are easy to make, and easy to consume. They have only fats lying in it causing ill effectson the health of the adolescents. The present study was done to assess the knowledge and practice of fastfood consumption and hazards on health among adolescents.Materials and methods: The study design adopted was descriptive in the colleges of urban area, where100 college students were participated through convenience sampling technique. Semi-structured selfadministered questionnaire were used to collect the data.Result:The findings revealed that10 % of the participants had inadequate knowledge, 28% of the participantshad moderate knowledge and 62% of the participants had adequate knowledge about fast food consumption.Respondents stated that that majority of participants (85%) eat restaurant fast food regularly and 51 % ofsubjects frequently eat fast food. The main reason for having fast food was its Flavourful taste, as per 64%respondents had replied.Conclusion: Though fast foods are tasty they have low nutritive value and high calories. Awarenessregarding the significance of a balanced diet and harmful effects of fast foods may help to reduce the fastfood addiction.